PERAN ASEAN COORDINATING CENTRE FOR HUMANITARIAN ASSISTANCE ON DISASTER MANAGEMENT (AHA CENTRE) DALAM KRISIS PASCA KUDETA DI MYANMAR PADA TAHUN 2021-2024 - Suhadi, M. Ali; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study examines the military coup that took place in Myanmar in February 2021 triggered a multidimensional humanitarian crisis characterized by escalating internal armed conflict, widespread human rights violations, mass displacement, and the collapse of basic public services. Within the context of Southeast Asia, this crisis has become a critical test for ASEAN as a regional organization that traditionally upholds the principles of non-interference and state sovereignty. This study aims to analyze the role of the ASEAN Coordinating Centre for Humanitarian Assistance on Disaster Management (AHA Centre) in responding to the humanitarian crisis in Myanmar during the post-coup period from 2021 to 2024. This research employs a qualitative approach using a literature review method, drawing on official ASEAN and AHA Centre reports, documents from international organizations, academic journals, theses, dissertations, and reputable media sources. The analytical framework of this study is grounded in constructivism, system-level analysis, and the concept of human security. Constructivism is utilized to examine how ASEAN norms, particularly the ASEAN Way with its emphasis on non-interference and consensus, shape and constrain the actions of the AHA Centre in responding to the Myanmar crisis. The system-level analysis explains how fragmentation within the global humanitarian governance regime and divergent interests among international actors affect ASEAN’s and AHA Centre’s operational space. Meanwhile, the human security perspective is applied to assess the extent to which AHA Centre’s response addresses concrete threats to human safety, including violence, food insecurity, displacement, and limited access to healthcare. The findings indicate that the AHA Centre has played a significant role as a humanitarian facilitator in Myanmar through logistical coordination, emergency aid distribution, and cooperation with ASEAN member states’ National Disaster Management Organisations (NDMOs). However, the effectiveness of these efforts remains severely constrained by structural, normative, and political factors. The dominance of the sovereignty principle and the AHA Centre’s reliance on the consent of Myanmar’s military junta have limited the reach of humanitarian assistance to the most vulnerable populations. This study concludes that while the AHA Centre contributes to maintaining ASEAN’s humanitarian presence in Myanmar, institutional reforms within ASEAN and a stronger human security-oriented approach are essential to enhance the effectiveness of future humanitarian responses. Keywords: : AHA Centre, ASEAN, Myanmar Military Coup, Humanitarian Crisis, Human Security.